Analisis Kemampuan Literasi Numerasi Peserta Didik SMP dalam Menyelesaikan Soal Cerita Aljabar - Banowati Amalia Putri; Dwi Priyo Utomo; Zukhrufurrohmah Zukhrufurrohmah (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2021)
This article describes junior high school students' literacy numeracy skills in solving story problems on algebra. The research was conducted at private-junior high school located in Batam with 25 female students' research subjects. The data were obtained through the literacy numeracy skills test and interview results, and then the data were analyzed using a qualitative descriptive study. The results showed that the literacy numeracy skills of 25 female students showed an excellent category with an average score of 84.7. Students with the highest score can fulfilled two to three indicators, while students with low score of literacy numeracy skills’ test only fulfilled one indicator. The unfulfillment of indicators is caused by student errors include: 1) Not writing known data information and asked, 2) Wrong in solving the problem, 3) Wrong when calculating, and 4) Not writing conclusions on the results of the answers obtained.